Riga Technical University Conference and Sports Centre «Ronīši» - Gudro, Ilze (History of Engineering Sciences and Institutions of Higher Education, 2020)
In 1958, when the Riga Polytechnic Institute (RPI) was renovated, the idea arose to create a sports and recreation camps, as well as a health camps for students, where after sessions they could relax and compete in various sports. RPI was one of the first Latvian higher education institutions to establish such bases. For the first time, the article summarizes and describes the development of the Riga Technical University (RTU) Conference and Sports centre «Ronīši» from the 1960s to the present day.